102 Levodopa and melanoma what do clinicians think?. Issue 9 (12th August 2022) - Symonds, Alexander; Davenport, Richard; Breen, David
Abstract : Parkinson's disease (PD) is associated with an increased risk of melanoma, but the link between levodopa therapy and melanoma is less clear. The Electronic Medicines Compendium (EMC) explicitly contraindi- cates prescribing levodopa in patients with current, or previous, melanoma despite the lack of convinc- ing evidence. To gauge clinical opinions on the perceived link between levodopa and melanoma, we disseminated a short online survey to neurology and geriatrics colleagues locally, as well as through the Association of British Neurologists and British Geriatrics Society. The majority of the 91 respondents were neurologists (84%), mostly consultants (69%). Most were not aware of guidance stating that levodopa should be contraindicated in patients with a history of melanoma (56%), and responded that they did not counsel for the risk of melanoma when initiating levodopa therapy (93%). Conversely, almost one quarter responded that they would not prescribe levodopa to PD patients with a history of melanoma (24%), the majority being non-movement disorder specialists. Six clinicians reported stopping levodopa therapy after the emergence of a suspicious skin lesion or melanoma (7%). In summary, clinicians are generally aware of the increased risk of melanoma in PD, but there is a lack of consensus on levodopa prescribing and counselling practices.